Automated and accelerated synthesis of indole derivatives on a nano-scale. Issue 2 (21st December 2018) - Shaabani, Shabnam; Xu, Ruixue; Ahmadianmoghaddam, Maryam; Gao, Li; Stahorsky, Martin; Olechno, Joe; Ellson, Richard; Kossenjans, Michael; Helan, Victoria; Dömling, Alexander
Abstract : Miniaturized and automated nanomole synthesis using acoustic dispensing technology dramatically accelerated the production of diverse libraries of three small molecule scaffolds. Abstract : Automated, miniaturized and accelerated synthesis for efficient property optimization is a formidable challenge in chemistry in the 21 st century as it helps to reduce resources and waste and can deliver products in shorter time frames. Here, we used for the first time acoustic droplet ejection (ADE) technology and fast quality control to screen the efficiency of synthetic reactions on a nanomole scale in an automated and miniaturized fashion. The interrupted Fischer indole combined with Ugi-type reactions yielded several attractive drug-like scaffolds. In 384-well plates, a diverse set of interrupted Fischer indole intermediates were produced and reacted with the tricyclic hydantoin backbone in a 2-step sequence. Similarly, preformed Fischer indole intermediates were used to produce diverse sets of Ugi products and the efficiency was compared with that of the in situ method. Multiple reactions were performed again on a preparative millimole scale, showing scalability from nano to mg and thus synthetic utility. An unprecedented large number of building blocks were used for fast scope and limitation studies (68 isocyanides, 72 carboxylic acids). Miniaturization and analysis of the generated big synthesis data enabled deeper exploration of the chemical space and permitted the gain of knowledge that was previously impractical or impossible, such as the rapid survey of reactions, and building block and functional group compatibility.